SAFETEL randomised controlled feasibility trial of a safety planning intervention with follow-up telephone contact to reduce suicidal behaviour: study protocol. Issue 2 (5th February 2019) - O'Connor, Rory C; Lundy, Jenna-Marie; Stewart, Corinna; Smillie, Susie; McClelland, Heather; Syrett, Suzy; Gavigan, Marcela; McConnachie, Alex; Smith, Michael; Smith, Daniel J; Brown, Gregory K; Stanley, Barbara; et al.
Abstract : Introduction: There are no evidence-based interventions that can be administered in hospital settings following a general hospital admission after a suicide attempt. Aim: To determine whether a safety planning intervention (SPI) with follow-up telephone support (SAFETEL) is feasible and acceptable to patients admitted to UK hospitals following a suicide attempt. Methods and analysis: Three-phase development and feasibility study with embedded process evaluation. Phase I comprises tailoring an SPI with telephone follow-up originally designed for veterans in the USA, for use in the UK. Phase II involves piloting the intervention with patients (n=30) who have been hospitalised following a suicide attempt. Phase III is a feasibility randomised controlled trial of 120 patients who have been hospitalised following a suicide attempt with a 6-month follow-up. Phase III participants will be recruited from across four National Health Service hospitals in Scotland and randomised to receive either the SPI with telephone follow-up and treatment as usual (n=80) or treatment as usual only (n=40). The primary outcomes are feasibility outcomes and include the acceptability of the intervention to participants and intervention staff, the feasibility of delivery in this setting, recruitment, retention and intervention adherence as well as the feasibility of collecting the self-harm re-admission to hospital outcome data. Statistical analyses will include description of recruitment rates, intervention adherence/use, response rates and estimates of the primary outcome event rates, and intervention effect size (Phase III). Thematic analyses will be conducted on interview and focus group data. Ethics and dissemination: The East of Scotland Research Ethics Service (EoSRES) approved this study in March 2017 (GN17MH101 Ref: 17/ES/0036). The study results will be disseminated via peer-reviewed publication and conference presentations. A participant summary paper will also be disseminated to patients, service providers and policy makers alongside the main publication. Trial registration number: ISRCTN62181241 .